(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this study provided all molecular markers of Random amplified polymorphic (RAPD) successfully with the sixty five Iraqi date palm (Phoenix dactylifera L.) cultivars, which collected from Hilla city in Iraq, to determine fingerprinting, polymorphic value, and relationships among varieties of date palm cultivars, and also with the same type of cultivars. Data analysis of ten RAPD has been revealed. Number of amplified DNA fragments were (592) bands, polymorphism per all primers were (%64.2), primer efficiency was 0.1, and discriminatory value was (%0.09), which revealed a high percentage similarity about %67 to %100 between cultivars belong to the same variety. There are relationships with twenty four genotypes, divided in to two clusters, clusterΙ ranged distance from 0.74 to 1.30 represented(Maddany, Ashrasi, Greatli, Smeasmi and sukkary) and clusterII ranged distance from 0.25 to 0.60 which divided into three sub group, there are sub group I represented (Sultana, Khestawi, Breem, Sabb Drrah, Hamrawi, Brban, and Khadrawi), sub groupiesII represented (Zahdi, Tebarzal, Maktom, brahi, Chipchab and Fom Alrman), sub groupies III represented (Usta Umran, Nersi, Najdi, Guntar, Shwethi and Ghanami Ahmer).